2004
DOI: 10.1079/phn2004561
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and cognitive decline

Abstract: Objective: To investigate the possible role of diet in age-related cognitive decline (ARCD) and cognitive impairment of both degenerative (Alzheimer's disease, AD) and vascular (vascular dementia, VaD) origin. Design: Literature review. Results:In an elderly population of southern Italy with a typical Mediterranean diet, high energy intake of monounsaturated fatty acids (MUFA) appeared to be associated with a high level of protection against ARCD. In addition, dietary fat and energy in the elderly seem to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(100 citation statements)
references
References 56 publications
2
95
0
3
Order By: Relevance
“…Despite the fact that the causes of dementia are multifactorial, there is growing evidence that modifiable risk factors such as cardio-metabolic diseases and lifestyle play an important role; Thus, nutrition is a key role [120] [121] [117] [118]. The typical mechanisms of aging of brain cells show signs of atrophy, most of which are related to 3 main mechanisms, as explained (above) in setting up, namely, the decline in supply flow blood and, mitochondrial dysfunction (caused by oxidative stress), increasing inflammation of the patient's brain [107].…”
Section: Iii-2-2 Cognitive Function and Dementiamentioning
confidence: 99%
“…Despite the fact that the causes of dementia are multifactorial, there is growing evidence that modifiable risk factors such as cardio-metabolic diseases and lifestyle play an important role; Thus, nutrition is a key role [120] [121] [117] [118]. The typical mechanisms of aging of brain cells show signs of atrophy, most of which are related to 3 main mechanisms, as explained (above) in setting up, namely, the decline in supply flow blood and, mitochondrial dysfunction (caused by oxidative stress), increasing inflammation of the patient's brain [107].…”
Section: Iii-2-2 Cognitive Function and Dementiamentioning
confidence: 99%
“…In fact, these factors exert more influence on the prevalence of Alzheimer's disease than genetics 24 . Proof of this is recent research that showed that older immigrants living in the United States have a higher prevalence of Alzheimer's disease than individuals living in their countries of origin 25 .…”
Section: Alzheimer's Disease Risk and Protective Factorsmentioning
confidence: 99%
“…Therefore, when motivated and supported by health professionals, individuals can use lifestyle options to influence their late-life cognitive performance and risk of brain disorders 10,15,26 . Among these options, nutrition has drawn much attention as a growing amount of evidence suggests that it may be a key factor in the development of Alzheimer's disease 10,24 .…”
Section: Alzheimer's Disease Risk and Protective Factorsmentioning
confidence: 99%
“…When enzymes, mitochondria, and proteins are subjected to this phenomenon, they can give rise to metabolic disorders, inflammation in several parts of the organism (blood vessels, heart, kidneys, joints); when DNA undergoes oxidation, it can cause alterations in the genetic code and increase the risk of cancer. Early ageing of cells and the development of some serious diseases such as atherosclerosis, diabetes, multiple sclerosis, rheumatoid arthritis, pulmonary emphysema, cataract, Alzheimer and Parkinson's disease, senile dementia, breast-prostatecolon-skin cancer, have all been related to continuous oxidative damage to cells [16,29,30,51,52]. Oxidative damage can be partially prevented by adequate defense systems of the organism and the contribution of antioxidant substances from breast milk (in infants) and by diet sources (in particular fruit, vegetables and EVOO), which inactivate free radicals by donating protons [16,29,30,[51][52][53].…”
Section: Oxidation and Oxidative Stressmentioning
confidence: 99%
“…Early ageing of cells and the development of some serious diseases such as atherosclerosis, diabetes, multiple sclerosis, rheumatoid arthritis, pulmonary emphysema, cataract, Alzheimer and Parkinson's disease, senile dementia, breast-prostatecolon-skin cancer, have all been related to continuous oxidative damage to cells [16,29,30,51,52]. Oxidative damage can be partially prevented by adequate defense systems of the organism and the contribution of antioxidant substances from breast milk (in infants) and by diet sources (in particular fruit, vegetables and EVOO), which inactivate free radicals by donating protons [16,29,30,[51][52][53]. Since the first studies on the MD, the beneficial effects of EVOO have been attributed to the high content in oleic acid, the adequate contribution of linoleic acid (18:2, n À 6) and a-linolenic acid (18:3, n À 3) (which are present in a optimal ratio), and to the limited presence of SFA [15,54].…”
Section: Oxidation and Oxidative Stressmentioning
confidence: 99%